Effect of Skeletal Paracrine Signals on the Proliferation of Interzone Cells. (December 2021) - Thampi, Parvathy; Dubey, Rashmi; Lowney, Rachael; Adam, Emma N.; Janse, Sarah; Wood, Constance L.; MacLeod, James N.
Objective: Articular cartilage in mammals has limited intrinsic capacity to repair structural defects, a fact that contributes to the chronic and progressive nature of osteoarthritis. In contrast, Mexican axolotl salamanders have demonstrated the remarkable ability to spontaneously and completely repair large joint cartilage lesions, a healing process that involves interzone cells in the intraarticular space. Furthermore, interzone tissue transplanted into skeletal defects in the axolotl salamander demonstrates a multi-differentiation potential. Cellular and molecular mechanisms of this repair process remain unclear. The objective of this study was to examine whether paracrine mitogenic signals are an important variable in the interaction between interzone cells and the skeletal microenvironment. Design: The paracrine regulation of the proliferation of equine interzone cells was evaluated in an in vitro co-culture system. Cell viability and proliferation were measured in equine fetal interzone cells after exposure to conditioned medium from skeletal and nonskeletal primary cell lines. Steady-state expression was determined for genes encoding 37 putative mitogens secreted by cells that generated the conditioned medium. Results: All experimental groups of conditioned media elicited a mitogenic response in interzone cells. Fetal anlage chondrocytes ( P < 0.0001) and dermal fibroblasts ( P < 0.0001) conditioned medium showed a significantly higher mitogenic potential compared with interzone cells. Conditioned medium from bone marrow–derived cells elicited a significantly higher proliferative response relative to that from young adult articular chondrocytes ( P < 0.0001) or dermal fibroblasts ( P < 0.0001). Sixteen genes had expression patterns consistent with the functional proliferation assays. Conclusions: The results indicate a mitogenic effect of skeletal paracrine signals on interzone cells.